KAJIAN PEMAHAMAN AKAD MURABAHAH PADA ANGGOTA KOPERASI SYARIAH - Akhir, Khoiriyatul; Sula, Atik Emilia (Universitas Madura, 2023)
This study uses a qualitative method with a case study approach. This research aims to find out the understanding of murabahah contracts among members of Islamic Cooperatives. The research was conducted at KSPPS BMT Makin Amin. The research location is at Jalan Jambu Raya No. 79, Housing National Housing, Kamal District, Bangkalan. The data collection method is by conducting in-depth interviews and observing informants related to the research theme. Based on predetermined criteria, 18 informants were obtained, with the disbursement of 16 KSPPS members and 2 people from KSPPS BMT Makin Amin employees. The results of the study show that BMT Makin Amin members who are currently/have done murabahah financing are included in the understanding category. Based on the understanding indicators put forward by Anderson & Krathwohl (2010: 106) the informants in this study were included in the category of disconnection, exemplifying, classifying, summarizing, concluding, and being able to compare. factors that influence members' understanding of murabahah financing at BMT Makin Amin Factors include internal factors and external factors indicating that understanding factors affect the level of understanding of members of murabahah financing. This is because informants can receive or remember an understanding or knowledge previously obtained, then can provide explanations again in a different language. So that the understanding of BMT Makin Amin members on murabahah contracts is also influenced by the factors previously mentioned.